2022
DOI: 10.24815/jpsi.v10i1.21807
|View full text |Cite
|
Sign up to set email alerts
|

Development of Problem Based Learning Based E-modules in the form of Flipbooks on Environmentally Friendly Technology Materials As an Independent Learning Material for Students Especially Online Learning

Abstract: Problem solving skills are important to have in the 21st century. In the online learning period, students are required to be able to learn independently from home. However, in fact the motivation of students' learning has decreased. To facilitate students' self-learning during online learning, improving learning motivation and problem solving skills, teachers need to provide interesting learning materials. Therefore, this research aims to develop self-learning materials in the form of problem based learning e-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This online teaching and learning activity has been running for more than a year. Various studies have revealed that students during online learning experience a decrease in learning motivation to a decrease in learning outcomes (Jena, 2020;Munzil, et al, 2022;Rasmawan & Erlina, 2021). This also happened at SMPN 16 Malang.…”
Section: Introductionmentioning
confidence: 84%
“…This online teaching and learning activity has been running for more than a year. Various studies have revealed that students during online learning experience a decrease in learning motivation to a decrease in learning outcomes (Jena, 2020;Munzil, et al, 2022;Rasmawan & Erlina, 2021). This also happened at SMPN 16 Malang.…”
Section: Introductionmentioning
confidence: 84%
“…Utilization of technology as a communication medium can be seen from the hypertext group, namely software facilities in computers that are able to provide opportunities for developing information needed by users. Previous studies have stated that the use of software provides convenience in combining text, video, images, animation in e-modules (Fathirma'ruf et al 2021;Linda, Nufus, and Susilawati 2020;Munzil et al 2022;Purwoto 2022). The interactive aspect makes the module not only a passive object used by students but also a medium that provides opportunities for interaction between students and learning resources.…”
Section: Discussionmentioning
confidence: 99%
“…The practicum module can be used as a reference and module for students in carrying out practicals so that students increasingly understand the work steps that must be done. The practicum module can guide students who have difficulty during practicum so that practicum objectives can be achieved optimally (Munzil et al, 2022).…”
Section: Introductionmentioning
confidence: 99%